The most severely ill patients with ME/CFS in Denmark - Peter la Cour (Cogent Public Health)
A subset of patients suffering from ME/CFS (Myalgic encephalomyelitis/chronic fatigue syndrome) are severely ill, bedridden, and dependent on personal care. This study aims to describe the medical and social conditions of the most severely ill patients with ME/CFS in Denmark and the situation of their caregivers. Qualitative data were collected during 19 home visits to severely ill patients in Denmark. The patients interviewed were characterised by extremely low physical and mental functioning and longstanding illness. Relative to their dire condition, the participants received very little help from medical professionals and health services such as institutions and hospitals. There was an overall negative interaction with psychiatric interventions, and the relations between patients and the health system were generally characterised by mutual distrust. Social services were often dismissed, and obtaining the services was often described as more of a burden than a benefit. In conclusion, the most severely ill patients with ME/CFS and their caregivers must be characterised as a systematically neglected patient group not comparable to any other similarly ill group.